Art-making effect on emotions and stress - Vanegas-Farfano, Minerva; González, Mónica (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2014)
Two ways of art-making (distraction and expression of the event) are examined as a form of stress and mood regulation activity in undergraduate students (n=20). A present stressful situation is recalled by the participants as an induced situation and the assigned to one of four conditions. Stress and affect were mesured before and after de assigned activity. Results reveals that stress and negative affect improved significantly in the distraction condition. The result indicates a probably association between art-making as a stress management activity and regular coping strategies.
Keywords: Art-making; Stress coping; Emotion regulation.